Transcriptional Regulation of the Murine Urokinase-type Plasminogen Activator Gene in Skeletal Myoblasts - Miralles, Francesc; Ibáñez-Tallon, Inés; Parra, Maribel; Crippa, Massimo; Blasi, Francesco; Besser, Daniel; Nagamine, Yoshikuni; Muñoz-Cánoves, Pura (Thrombosis and Haemostasis, 1999)
We have previously shown that urokinase-type plasminogen activator (uPA) is highly expressed in murine C2C12 myoblasts and that antibodies against uPA are able to block both myoblast fusion and differentiation. Here we show the characterization of cis-acting elements in the mouse uPA promoter in vitro which are involved in uPA gene expression in C2C12 myoblast cells. DNase I hypersensitive (HS) site analysis revealed the presence of three HS sites in myoblasts. Deletion analysis of stably transfected uPA-promoter constructs revealed that at least two of the three HS sites accounted for the high transcriptional expression in C2C12 cells. One was located at -2.4 kb and corresponded to a known PEA3/AP1A element and the other one was located at -4.9 kb and contained a CArG box and a CRE element. So far, no regulatory function had been assigned to this CRE/CArG element. Both HS sites alone were able to activate transcription of a heterologous promoter and showed a cooperative effect when placed together. Electrophoretic mobility-shift assays using myoblast nuclear extracts and specific antibodies demonstrated that cJun, JunD and ATF2 bound to the PEA3/AP1A element, whereas the CRE/CArG element bound SRF. Altogether, these results suggest that high uPA expression in myoblasts is dependent on the cooperation of two regulatory sites in the uPA promoter.